Trends in Mortality From Aortic Stenosis in Europe: 2000–2017 - Hartley, Adam; Hammond-Haley, Matthew; Marshall, Dominic C.; Salciccioli, Justin D.; Malik, Iqbal S.; Khamis, Ramzi Y.; Shalhoub, Joseph (Frontiers in Cardiovascular Medicine, 2021)
Background: Trends in mortality from aortic stenosis across European countries are not well-understood, especially given the significant growth in transcatheter aortic valve implantation (TAVI) in the last 10 years. Methods: Age-standardised death rates were extracted from the World Health Organisation Mortality Database, using the International Classification of Diseases 10th edition code for non-rheumatic aortic stenosis for those aged > 45 years between 2000 and 2017. The UK and countries from the European Union with at least 1,000,000 inhabitants and at least 50% available datapoints over the study period were included: a total of 23 countries. Trends were described using Joinpoint regression analysis. Results: No reductions in mortality were demonstrated across all countries 2000–2017. Large increases in mortality were found for Croatia, Poland and Slovakia for both sexes (>300% change). Mortality plateaued in Germany from 2008 in females and 2012 in males, whilst mortality in the Netherlands declined for both sexes from 2007. Mortality differences between the sexes were observed, with greater mortality for males than females across most countries. Conclusions: Mortality from aortic stenosis has increased across Europe from 2000 to 2017. There are, however, sizable differences in mortality trends between Eastern and Western European countries. The need for health resource planning strategies to specifically target AS, particularly given the expected increase with ageing populations, is highlighted.